Asymmetric Information: Tinjauan Berdasarkan Rekomendasi Analis Sekuritas dan Revisi Earning Forecast - Cicilia Erna Susilawati (Ekonomis: Journal of Economics and Business, 2020)
Trading in the stock market occur due to differences in opinion on the expected value of the securities. In the other side, asymmetric information between investors and companies caused the stock price does not reflect the real price. So, asymmetric information should be reduced. Information by securities analysts is an information that is expected to reduce that. This study investigates the performance of securities analysts through its role in reducing asymmetric information. This is motivated by some previous studies that stated that the Indonesian capital market is inefficient, because high levels of asymmetric information. Analysts is considered as inform market participant who can reduce the asymmetric information so as to make capital market to be efficient. The role of securities analysts is seen through the product. There are stock recommendation and earnings forecast revision. Testing the consistency of the analyst's stock recommendations and earnings forecast revision before testing their impact on asymmetric information. The results showed that output in the form of stock securities analysts and earnings forecast recommendation are consistent but has not been able to reduce the asymmetry of information that occurs between investors and companies.